Heterodoxias y distorsiones en el arte en torno al Camino de Santiago - Momplet Míguez, Antonio E. (Revista de Filología Románica, 2006)
The article describes and analyzes several questions about art associated to the pilgrimage way to Santiago, specially focusing on medieval examples. Some aspects of these art works might seem surprising if considered from strictly orthodox perspectives, but can be explained related to their contemporary historical, artistic and cultural context. Cases referred are discussed in three groups: examples of iconography, reliquaries, and Spanish Islamic works of art.
Keywords: Pilgrimage; Way of Saint James (Camino de Santiago); Iconography; Medieval Art; Romanesque Art; Spanish Islamic Art; Reliquaries